Teachers’ assessment practice during distance education: Analysis of the data on online learning experiences in middle schools in the Veneto Region - Paramatti, Silvia; Zaggia, Cristina; Doria, Beatrice; Grion, Valentina (Formazione & insegnamento, 2023)
The empirical research begins by analyzing SIRD’s survey of school practices during the school closure caused by COVID-19 pandemic. New research questions emerged from this analysis: we designed a study to investigate whether assessment practices, including those supported by technology, were maintained upon return to the classroom. Specifically, the goal of the research is to promote awareness of what has changed during and after the lockdown (over a period of about two years). Through the data obtained, this study emphasizes that effective practices have been put in place and that some of them are currently being integrated while others could be integrated in the future.